In Situ Resource Utilization (ISRU) field expedition 2012: Near-Infrared Volatile Spectrometer System (NIRVSS) science measurements compared to site knowledge. Issue 10 (15th May 2015) - Roush, Ted L.; Colaprete, Anthony; Elphic, Richard; Ennico-Smith, Kimberly; Heldmann, Jennifer; Stoker, Carol; Marinova, Margarita; McMurray, Robert; Fritzler, Erin; Morse, Stephanie
Abstract The scientific information collected and evaluated using the Near-Infrared Volatile Spectrometer System (NIRVSS) during the 2012 In Situ Resource Utilization (ISRU) field campaign, exhibits variations related to differing surface materials and presence of volatiles during both rover traverses and auger activities demonstrating the promise of using NIRVSS for volatile prospecting on the lunar surface.